Spread of the Introduced Sitka Spruce (Picea sitchensis) in Coastal Norway - Per Nygaard; Bernt-Håvard Øyen (Forests, 2017)
Positive and negative effects on ecosystem services from plantation forestry in Europe have led to conflicts regarding non-native tree species. Sitka spruce (Picea sitchensis (Bong.) Carr.) is the most common plantation species in northwest Europe, covering 1.3 Mha. In costal Norway, Sitka spruce was intentionally introduced and is currently occupying about 50,000 ha. Sitka spruce was blacklisted in Norway in 2012, mainly based on the risk for invasive spreading, but little quantitative documentation exists on spread. Here we quantify spread from plantations into abandoned heathland and pastures in thirteen sites where natural regeneration occurs. Spread distances and zero-square distributions related to the nearest edge of the parent stand were fitted by use of Weibull. The median expansion rate was 0.8 m·year−1 in north Norway and 4.4 m·year−1 in west Norway. The maximum establishment distance measured was 996 m. A peak in sapling density occurred within 50 m from the edge, and there was a general decrease in saplings with increasing distance. Conversely, increase in zero-squares percentages occurred with increasing distance. We argue that inclusion of abundance in assessing spread is necessary to define invasiveness. Based on spread models and prevailing forestry practices we recommend that the establishment of new Sitka spruce plantations within 200 m of protected areas should be avoided.